Drug utilization study in ophthalmology in OPD patients at a tertiary care teaching hospital - Bhatt, Jigar H.; Verma, Shashwat; Bagde, Srushti; Sane, Rohit M.; Shahani, Savita (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drug therapy is a major component of patient care management in health care settings. Irrational and inappropriate use of drugs in health care system observed globally is being a major concern. In the field of ophthalmology, there have been many drug developments and different classes of drugs with combinational products are available in ophthalmology for the treatment of ophthalmic diseases. Periodic prescription analysis in the form of drug utilization study can improve the quality of prescription and curb the menace of irrational prescribing. Aim and objectives were to study the prescribing pattern and drug utilization trends in Ophthalmology outpatient department at a tertiary care hospital in Navi Mumbai. Methods: A cross-sectional, observational study was conducted over a period of six months in Ophthalmology department of a tertiary care teaching hospital, Navi-Mumbai. A total of 103 adult patients visiting Ophthalmology OPD for curative symptoms were included and their prescriptions were analyzed with WHO prescribing indicators and additional indices. Results: Analysis showed that the average number of drugs per prescription was 1.9. Percentage of drugs prescribed by brand was 100 % versus generic 0 %. Percentage of drugs prescribed from National Essential drug list (NEDL) was 53%. The percentage of encounters with antibiotics was 30.6%. The commonest prescribed drugs were ocular lubricants followed by antibiotics. Eye drops were the commonest prescribed dosage form. Conclusions: Ocular lubricants and antibiotics dominated the prescribing pattern in this study with restraint on polypharmacy, but showed ample scope for improvement in encouraging the ophthalmologist to prescribe generic and selection of essential drugs.